2017
DOI: 10.1007/s00267-017-0898-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Ground or in the Air? A Methodological Experiment on Crop Residue Cover Measurement in Ethiopia

Abstract: Maintaining permanent coverage of the soil using crop residues is an important and commonly recommended practice in conservation agriculture. Measuring this practice is an essential step in improving knowledge about the adoption and impact of conservation agriculture. Different data collection methods can be implemented to capture the field level crop residue coverage for a given plot, each with its own implication on survey budget, implementation speed and respondent and interviewer burden. In this paper, six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The presence of crop residue cover is hence interpreted as direct evidence for reduced or zero tillage. Unlike estimation of zero tillage adoption, self-reported data on the extent of crop residue cover is likely to be imprecise and is often either reported as a simple binary variable or as categorical variable with broad intervals of the extent of crop residue cover (Kosmowski et al 2017).…”
Section: Tillage and Crop Residue Covermentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of crop residue cover is hence interpreted as direct evidence for reduced or zero tillage. Unlike estimation of zero tillage adoption, self-reported data on the extent of crop residue cover is likely to be imprecise and is often either reported as a simple binary variable or as categorical variable with broad intervals of the extent of crop residue cover (Kosmowski et al 2017).…”
Section: Tillage and Crop Residue Covermentioning
confidence: 99%
“…The authors showed that SPOT-5 imagery can be used to detect crop residue cover and also stated that Sentinel-2 imagery would be a suitable replacement due to its wide swath, high temporal resolution, and higher number of bands. Kosmowski et al (2017) compared different methods of crop residue coverage measurement, including satellite imagery and household surveys. Survey data were collected from 197 households and 314 plots in Ethiopia.…”
Section: Tillage and Crop Residue Covermentioning
confidence: 99%
“…Data collection protocols for a subset of 18 research-related innovations for which background evidence suggested they had scaled were then integrated into the Ethiopian Socioeconomic Survey (ESS), a regionally and nationally representative household panel survey in 2015-2016 and 2018-2019. 3 Protocols were based on validation experiments and other measurement improvement work (Kosmowski et al 2017(Kosmowski et al , 2019 assuring that best-practice, objective, and reliable data were collected. These then yield credible estimates that between 4.1 and 11.0 million Ethiopian households had been reached by CGIAR-related innovations.…”
Section: Accurate Diffusion Data At a Policy-relevant Scalementioning
confidence: 99%